Legal Protection Regarding Losses Due To Default In Business Agreements In Office Stationery Companies - Silfiyah Silfiyah; Irma Maulida (Ann Publisher, 2026)
Background. This research examines the problem of default in business agreements at office stationery companies, particularly violations of contract clauses such as late delivery, non-compliance with goods, and violations of distribution area exclusivity. Aims. The main issues studied are forms of default and legal protection mechanisms for injured parties. This research aims to comprehensively analyze forms of default and legal protection efforts that can be taken in business practices. Methods. The method used is a normative juridical approach combined with an empirical approach through case studies. Data was obtained from statutory regulations, literature, and field data through interviews, observation, and documentation, then analyzed qualitatively using descriptive-analytical methods. Result. The research results show that default occurs in various forms, namely non-fulfillment of obligations, delays in implementation, non-performance, and violations of exclusivity clauses. The impacts include material and immaterial losses, including decreased sales and loss of consumer confidence. Conclusion. Legal protection can be achieved through non-litigation or litigation, such as negotiation, mediation, and compensation claims. Implementation. However, implementation has not been optimal due to weaknesses in contract preparation. Therefore, clearer contracts, strict sanctions and effective dispute resolution mechanisms are needed to ensure legal certainty and the continuity of business relationships.